Comparative analysis: nationalism and resistance in Chinua Achebe’s Things Fall Apart and Bankim Chandra Chatterjee’s Anandamath. - Subha, Jarin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2024.